OPTIMIZATION OF INNOVATION AND INVESTMENT PROCESSES OF THE ENTERPRISE BASED ON THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Гавриленко, Наталія Г.; Олійник, Олег В. (Journal of Strategic Economic Research, 2023)
The article proposes optimization of the enterprise's innovation and investment processes based on the use of information and communication technologies. It is highlighted that flexibility in the management of innovation and investment processes at the enterprise should be manifested not only at the stage of formation of innovation and investment potentials, but also at the stage of their implementation. The conducted retrospective analysis of management models of the innovation-investment process made it possible to identify the following trends that characterize it at the current stage: (1) effective communications of the enterprise with the external environment; (2) increasing the role of knowledge and learning; (3) using the principles of "open innovation"; (5) creation of innovative ecosystems; (5) digitalization of the innovation and investment process. According to the results of the analysis, the concept of innovation and investment process based on the use of information and communication technologies was added. It is emphasized that interaction with the external environment and effective communication with it at various levels and in various forms, which allows to achieve a synergistic effect, plays a special role in the formation of the innovative and investment potential of the enterprise in today's conditions. It was highlighted that the priority direction of development is the end-to-end digitalization of all processes at the enterprise, ecosystems and states based on the introduction of information and communication technologies. In order to implement effective management and optimization of innovation and investment processes at the enterprise, it is proposed to use a system of balanced indicators, adapted taking into account the tasks of information and communication technologies.